2018
DOI: 10.1093/molbev/msy024
|View full text |Cite
|
Sign up to set email alerts
|

Selection and Neutral Mutations Drive Pervasive Mutability Losses in Long-Lived Anti-HIV B-Cell Lineages

Abstract: High-affinity antibodies arise within weeks of infection from the evolution of B-cell receptors under selection to improve antigen recognition. This rapid adaptation is enabled by the distribution of highly mutable “hotspot” motifs in B-cell receptor genes. High mutability in antigen-binding regions (complementarity determining regions [CDRs]) creates variation in binding affinity, whereas low mutability in structurally important regions (framework regions [FRs]) may reduce the frequency of destabilizing mutat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 52 publications
0
17
0
Order By: Relevance
“…Phylogenetic techniques have been used to study B cell lineages for many years (49) and continue to be a powerful tool in understanding affinity maturation (50). Two fundamental issues that arise from the application of phylogenetic techniques to B cell repertoires are 1) the biology underlying B cell affinity maturation violates key assumptions of most phylogenetic models and 2) phylogenetic models are designed typically to work on lineages originating from a common ancestor, but B cell repertoires are composed of multiple lineages with separate ancestries, many of which are composed of only a few unique sequences.…”
Section: Discussionmentioning
confidence: 99%
“…Phylogenetic techniques have been used to study B cell lineages for many years (49) and continue to be a powerful tool in understanding affinity maturation (50). Two fundamental issues that arise from the application of phylogenetic techniques to B cell repertoires are 1) the biology underlying B cell affinity maturation violates key assumptions of most phylogenetic models and 2) phylogenetic models are designed typically to work on lineages originating from a common ancestor, but B cell repertoires are composed of multiple lineages with separate ancestries, many of which are composed of only a few unique sequences.…”
Section: Discussionmentioning
confidence: 99%
“…Sheng et al found specific hotspots in anti-HIV B cell receptors which are initially highly variable and lose their mutability over time (115). Vieira et al showed that this loss of mutability is caused by a 60% greater frequency of mutability losses than gains (116) and Hoehn and colleagues developed a substitution model that represents the decay of the mutation rate of B-cell lineages over time, starting from a known germline sequence (117). These studies demonstrate how the rules that shape immune repertoires are starting to be uncovered and understood.…”
Section: Computational Tools Can Elucidate the Laws That Shape Immune Repertoiresmentioning
confidence: 99%
“…Analysis of phylogentic trees build from RepSeq data from HIV patients combined with S5F hypermutation models [240] also led to identifying the constraints on BCR adaptation [266]. Ancestral sequences in lineages are more likely to mutate their CDR3s than the framework (FWR).…”
Section: Evolutionary Analysis Of Repertoire Dynamicsmentioning
confidence: 99%